2010
DOI: 10.1051/0004-6361/200912184
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of refractory and volatile elements in CoRoT exoplanet host stars

Abstract: The relative distribution of abundances of refractory, intermediate, and volatile elements in stars with planets can be an important tool for investigating the internal migration of a giant planet. This migration can lead to the accretion of planetesimals and the selective enrichment of the star with these elements. We report on a spectroscopic determination of the atmospheric parameters and chemical abundances of the parent stars in transiting planets . Adding data for CoRoT-3 and CoRoT-5 from the literature,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Independent of the source of this peculiar abundance pattern, the signature of such condensation/accretion processes will still leave a greater imprint if the star convective envelope is considerably smaller than usually expected for solar type stars at ages <10 Myr. Also, the analysis of Chavero et al (2010) reveals no obvious correlation between abundances and condensation temperatures in the CoRoT stars, indicating no sign of overabundance of volatiles relative to refractories in stars harboring close-in giant planets compared to the Sun, contradicting the observations of Melendez et al (2009) and Ramirez et al (2009). The peculiar abundance ratio determinations in the Sun and solar analogs without detected giant planets must thus be confirmed by further studies.…”
Section: Abundances In Planet Host Starsmentioning
confidence: 75%
See 1 more Smart Citation
“…Independent of the source of this peculiar abundance pattern, the signature of such condensation/accretion processes will still leave a greater imprint if the star convective envelope is considerably smaller than usually expected for solar type stars at ages <10 Myr. Also, the analysis of Chavero et al (2010) reveals no obvious correlation between abundances and condensation temperatures in the CoRoT stars, indicating no sign of overabundance of volatiles relative to refractories in stars harboring close-in giant planets compared to the Sun, contradicting the observations of Melendez et al (2009) and Ramirez et al (2009). The peculiar abundance ratio determinations in the Sun and solar analogs without detected giant planets must thus be confirmed by further studies.…”
Section: Abundances In Planet Host Starsmentioning
confidence: 75%
“…Although interesting, however, this interpretation of the peculiar refractory to volatile abundance ratio in the Sun and other solar twins without detected close-in giant planets as a consequence of terrestrial planet formation is challenged by the recent analysis of Chavero et al (2010), based on four CoRoT planet host stars. This work suggests that alteration of abundances of refractories with respect to volatiles in stellar atmospheres may simply result from condensation processes in the accretion disk and from accretion of such altered gas onto the star.…”
Section: Abundances In Planet Host Starsmentioning
confidence: 99%
“…nitrogen, oxygen, and some refractory metals, would also expand the analysis to a larger context. Indeed, the investigation of volatile and refractory elements with respect to the distribution of their abundances in function of the condensation temperature (T C ) will shed light on recent controversies aroused by Chavero et al (2010). The flat distribution found by these authors should be confirmed with more precise abundance determination for T C 300 K (which includes C, N, and O).…”
Section: Discussionmentioning
confidence: 92%
“…The abundance computation was done using the MOOG program (abfind driver) in combination with the LTE Kurucz model atmosphere previously calculated with FUNDPAR. The line-list and atomic parameters for most of the elements were compiled from Neves et al (2009) and from Chavero et al (2010) for Zn and Ba. We emphasize that for ions such as Na, Mg, Al, Sc i, Cr ii, Zn and Ba ii the line-list comprises only two or three lines and therefore the conclusions involving these species should be taken with caution.…”
Section: Chemical Analysismentioning
confidence: 99%